How well are children with autism spectrum disorder doing academically at school? An overview of the literature. (April 2016) - Keen, Deb; Webster, Amanda; Ridley, Greta
The academic achievement of individuals with autism spectrum disorder has received little attention from researchers despite the importance placed on this by schools, families and students with autism spectrum disorder. Investigating factors that lead to increased academic achievement thus would appear to be very important. A review of the literature was conducted to identify factors related to the academic achievement of children and adolescents with autism spectrum disorder. A total of 19 studies were identified that met the inclusion criteria for the review. Results indicated that many individuals demonstrate specific areas of strength and weakness and there is a great deal of variability in general academic achievement across the autism spectrum. Adolescents and individuals with lower IQ scores were underrepresented, and few studies focused on environmental factors related to academic success. The importance of individualised assessments that profile the relative strengths and weaknesses of children and adolescents to aid in educational programming was highlighted. Further research on child-related and environmental factors that predict academic achievement is needed.